2009
DOI: 10.1111/j.1365-2621.2009.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot air drying of yacon (Smallanthus sonchifolius) and its effect on sugar concentrations

Abstract: This work aimed to experimentally study the drying behaviour of yacon tubers with and without steam blanching. Drying was carried out for 5 h and 30 min in a forced air dryer at 50°C, 60°C and 70°C. The results indicated that the shortest drying time was obtained at 70°C for blanched samples, and that the equilibrium water activity values were significantly lower for the blanched samples at all temperatures. The yacon dried without prior blanching showed lowest concentrations of reducing sugars when dried at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 27 publications
6
33
2
2
Order By: Relevance
“…In the in natura yacon pulp, moisture content was close to the values found in the literature, which are between 81.7% and 88.7% (LAGO, 2010;SCHER;NOREÑA, 2009;MARANGONI, 2007).…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…In the in natura yacon pulp, moisture content was close to the values found in the literature, which are between 81.7% and 88.7% (LAGO, 2010;SCHER;NOREÑA, 2009;MARANGONI, 2007).…”
Section: Methodssupporting
confidence: 65%
“…The PER enzymatic activity was also higher in the peel when compared to that of the yacon pulp. Besides, the enzymatic activity of PER in the in natura yacon pulp was higher than that found by Scher, Rios and Noreña (2009) in the same product, 22.0 U.g -1 .min -1 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These values were in accordance with Manrique et al (2005) who reported that about 85 to 90% of the fresh weight of yacon consisted of water and with Scher et al (2009) who found moisture of 88.69 ± 0.10%, soluble solids of 9.9 ± 0.01 °Brix and pH 6.09 ± 0.02. Figure 1 presents the mass loss of the samples over time for the four solutes used in this work.…”
Section: Yacon Compositionsupporting
confidence: 80%
“…The saccharides content (FOS, glucose and fructose) in final NF-retentate was evaluated by the high performance liquid chromatography (HPLC) as described by Zuleta and Sambucetti (2001) and Scher et al (2009), using a Perkin Elmer series 200 chromatograph equipped with a refractive index detector (HPLC-RI) (PerkinElmer Life and Analytical Sciences, Shelton, CT, USA) and ultrapure water as the mobile phase at 0.6 mL.min -1 , temperature of 80°C and a Phenomenex Rezex RHM monosaccharide column, 330 mm·7.8 mm, with a total run time of 14 min. Reference sugars (glucose, fructose and inulin) were purchased from Sigma-Aldrich.…”
Section: Saccharides Content Determination By Hplcmentioning
confidence: 99%